Empowerment Communication for Persons with Disabilities A Case Study of Caffe Lubi.co - Maulia, Mita; Waskito, Budhi; Pienrasmi, Hanindyalaila (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study discusses the role of empowerment communication in enhancing the abilities of deaf-mute individuals at Caffe Lubi in preparing for the world of work. The background of this research is rooted in the ongoing challenges faced by people with disabilities—particularly those who are deaf-mute—in Indonesia, including discrimination and limited access to employment opportunities, despite their significant presence in the national population. This study aims to provide an in-depth description of the empowerment communication processes implemented at Caffe Lubi and their impact on the development of work-related skills and personal independence among deaf-mute individuals. A descriptive qualitative method with a case study approach was employed, focusing on Caffe Lubi. Data were collected through observation, interviews, and documentation involving three deaf-mute individuals working at the café. The findings reveal that empowerment communication at Caffe Lubi is conducted through two-way interactions between facilitators and persons with disabilities, the use of sign language, and written communication tools. This process has proven effective in improving both soft skills—such as teamwork, time management, and problem-solving—and hard skills, including barista techniques, inventory management, and the use of office software for administrative tasks. The empowerment initiatives at Caffe Lubi not only enhance vocational competencies but also foster self-confidence and independence among deaf-mute individuals, equipping them to adapt in the workplace both as employees and as potential entrepreneurs. This research underscores the importance of inclusive and supportive communication in empowering people with disabilities, ultimately contributing to equal employment opportunities and a more disability-friendly work environment.